**(1 + a)**^{6}

= ^{6}C_{0} 1 a^{0} + ^{6}C_{1} . 1 . a^{1} + ^{6}C_{2} . 1 . a^{2} + ^{6}C_{3} . 1 . a^{3} + ^{6}C_{4}. 1 .a^{4} + ^{6}C_{5} . 1 . a^{5} + ^{6}C_{6} 1 . a^{6}

= 1 + 6a + 15a^{2} + 20a^{3} + 15a^{4} + 6a^{5} + a^{6}

LHS = (1 + a)^{6}

Putting a = 2.

LHS = (1 + 2)^{6} = (3)^{6} = 729

RHS = 1 + 6a + 15a^{2} + 20a^{3} + 15a^{4} + 6a^{5} + a^{6}

Putting a = 2.

RHS= 1 + 6 × 2 + 15(2)^{2} + 20(2)^{3} + 15(2)^{4} + 6(2)^{5} + (2)^{6}

= 1 + 12 +(15 × 4) + (20 × 8) + (15 × 16) + 6(32) + 64

= 13 + 60 + 160 + 240 + 192 + 64

= 729

Hence, LHS = RHS